Le Marche De Gros De L’igname Kponan A Abidjan (Côte D’ivoire) - Kouakou, Kouakou Philipps; Kouassi, Charles Aimé; Anoh, Kouassi Paul (European Scientific Journal, ESJ, 2019)
With an annual production of 7 148 000 tons in 2017, yams are the leading food crop in Côte d'Ivoire. The cultivated species are Dioscorea alata and Dioscorea cayenensis-rotundata. From the latter, the Kponan variety is particularly popular in several urban centers, espacially Abidjan, the economic capital. Through a documentary research and a questionnaire survey conducted in four municipalities, this article aims to understand the commercial circuit of Kponan yam in Abidjan, precisely the wholesale market, as well as the actors who run it. The data collected show that the wholesale market for Kponan yams in Abidjan is based on interaction between several actors. At the beginning, there are marketers who act as a link between peasant producers and wholesale traders, relying on transporters. The supply areas are mainly made up of two regions, all located in the north-east of the country. These are Bondoukou and Bouna, which account for 60 and 33,3% respectively of the volume of Kponan yams sold on the wholesale market in Abidjan. The selling prices are set by integrating a profit margin of 100 to 150 CFA francs/kg from the direct seller to the wholesaler and 50 to 100 CFA francs/kg from the wholesaler to the retailer. This translates into prices of 300- 350 CFA francs/kg in periods of abundance and 400-450 CFA francs in periods of scarcity (wholesale market price). The average annual volume marketed per wholesaler is 776.8 tonnes, which corresponds to a turnover ranging between 243 146 500 and 281 986 500 CFA francs. Avec une production annuelle de 7 148 000 tonnes en 2017, l’igname est la première culture vivrière en Côte d’Ivoire. Les espèces cultivées sont les Dioscorea alata et Dioscorea cayenensis-rotundata. Issue de la dernière, la variété Kponan est particulièrement prisée de plusieurs centres urbains, notamment Abidjan, la capitale économique. A travers une recherche documentaire et une enquête par questionnaire réalisée dans quatre communes, cet article vise à comprendre le circuit commercial de l’igname Kponan à Abidjan, précisément le marché de gros, ainsi que les acteurs qui l’animent. Il ressort des données recueillies que le marché de gros de l’igname Kponan à Abidjan repose sur une interaction entre plusieurs acteurs. Au départ, il y a les démarcheurs qui assurent la liaison entre les producteurs paysans et les commerçants grossistes en s’appuyant sur les transporteurs. Les zones d’approvisionnement sont principalement constituées de deux régions toutes localisées au Nord-Est du pays. Il s’agit de Bondoukou et Bouna qui concentrent respectivement 60 et 33,3% du volume d’igname Kponan vendu sur le marché de gros à Abidjan. Les prix de vente sont fixés en intégrant une marge bénéficiaire de 100 à 150 FCFA/kg du démarcheur au commerçant grossiste et de 50 à 100 FCFA/kg du grossiste au détaillant. Cela se traduit par des prix de 300-350 FCFA/kg en période d’abondance et de 400-450 FCFA en période de rareté (prix pratiqué au marché de gros). Le volume moyen annuel commercialisé par grossiste est de 776,8 tonnes, ce qui correspond à un chiffre d’affaire oscillant entre 243 146 500 et 281 986 500 FCFA.